2021
DOI: 10.1089/jpm.2020.0547
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Access and Scope of Services for Undocumented Immigrants: A Clinician Survey

Abstract: Objectives: To characterize clinician experiences of hospice access and scope of services for undocumented immigrants. Background: The 10.5 million undocumented immigrants in the United States are not covered by Medicare's hospice benefit and are at high risk for being uninsured. Limited data are available regarding hospice services for this population. Setting/Subjects: Two hundred ninety-four interdisciplinary palliative care clinicians from across the United States. Measurements: Participants completed a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recent studies have revealed structural aspects of the American healthcare system which create challenges for Latinx patients. 35,37,38,48 Clinicians and healthcare systems need to change practice patterns that negatively affect Latinx patient trust and satisfaction. 26,49 Many of these changes focus on improving communication and time spent with patients in clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed structural aspects of the American healthcare system which create challenges for Latinx patients. 35,37,38,48 Clinicians and healthcare systems need to change practice patterns that negatively affect Latinx patient trust and satisfaction. 26,49 Many of these changes focus on improving communication and time spent with patients in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey completed by 294 palliative care physicians, 68% endorsed that limited or no hospice options exist for undocumented immigrant patients. 37 Another 2007 survey showed that undocumented status was associated with lower likelihood of a blood pressure check in the preceding 2 years, lower likelihood of cholesterol check in the past 5 years, and lower likelihood of receiving healthcare information from a doctor. 38 Cultural Traditions.…”
Section: Latinx Patient Challengesmentioning
confidence: 99%
“…Hospice has now been part of the American landscape of end‐of‐life care for more than forty years. Medicare financing based on diagnosis and prognosis makes hospice accessible to nearly everyone who meets enrollment criteria 3 . The hospice movement, scope of services, eligibility criteria, and financing mechanism were originally developed based on the needs of people with end‐stage cancer.…”
Section: Essaysmentioning
confidence: 99%
“…Emergency Medicaid funding for hospice and palliative care is also limited, with a survey of palliative clinicians in the US finding that hospice was limited or unavailable for over two-thirds of undocumented people in their practice. 7 The limited hospice facilities that accept undocumented immigrants are often overwhelmed with patients.…”
Section: Healthcare Systemsmentioning
confidence: 99%